Anatomy of the Skull of Saanen Goat. An anesthesiology and Stereology Approach - Wang,Xiangyang (Sociedad Chilena de Anatomía, 2021)
SUMMARY: The Saanen goat is known as the greatest milk producer among small ruminat breeds. However, its morphometric features still remain unclear. Therefore, the present work aimed to investigate the functional anatomy of the upper and lower jaws as well as the volumetric properties of the male and female Saanen goat for clinical applications. The heads of 20 adult animals (10 males and 10 females) were included. Totally, 22 morphometric parameters were measured on three dimensional computed tomographic images using RadiAnt DICOM Viewer software and some parameters were measured on hot macerated sample. The mean volume of paranasal sinuses as well as conchal sinuses were estimated using stereological method. Based on the results, the differences between males and females were not significant (p>0.05) in all desired parameters.The frontal and lacrimal sinuses were the largest and smallest paranasal sinus in both sexes. Also, the dorsal and middle conchal sinuses were the largest and smallest ones, respectively. The common nasal meatus was the smallest and ventral meatus was the largest meatus in the nasal cavity. In conclusion, these findings provide a basic data that would be useful in blocking terminal branches of the cranial nerves in this breed for surgical purpose or teeth injuries treatment.